Laser selective melting forming method for large-particle-size copper and copper alloy powder

By using two laser scanning methods in SLM technology, the problems of low efficiency and high cost of powder forming of large-particle copper alloys are solved, and efficient dense forming and low-cost forming are achieved.

CN119772201AActive Publication Date: 2025-04-08GRINM ADDITIVE MFG TECH CO LTD

Patent Information

Application Number
CN202411980827.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing SLM technology has problems such as low forming efficiency, low utilization, high cost and many metallurgical defects when forming large-particle copper alloy powders.

Method used

A laser selection melting forming method of large-particle copper and copper alloy powder is adopted, and two laser scans are used: the first laser scan forms the initial melting layer, and the second laser scan increases the energy density to obtain a dense molding layer.

Benefits of technology

It realizes efficient dense forming of large-particle metal powder, reduces the cost and energy density of SLM technology, improves the forming efficiency, and reduces metallurgical defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119772201A_ABST
    Figure CN119772201A_ABST
Patent Text Reader

Abstract

The invention relates to a laser selective melting forming method for large-particle-size copper and copper alloy powder. The laser selective melting forming method comprises the steps of raw material powder laying and laser scanning. The granularity D of the raw material powder is more than or equal to 50 microns and less than or equal to 250 microns, D90 is more than or equal to 100 microns and less than or equal to 200 microns, and the powder paving thickness t is more than or equal to 0.5 D90 + A, and A is more than or equal to-10 microns and less than or equal to 10 microns; the laser scanning comprises first-time laser scanning and second-time laser scanning; through two times of laser scanning with different energy densities, an initial melting layer is firstly formed, and then a compact forming layer is obtained. The relative density of the target sample prepared through the method is larger than 99%, and compared with SLM forming with the conventional particle size in the prior art, the SLM technology forming cost is greatly reduced, the SLM forming efficiency is improved, and the energy density needed by SLM is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal 3D printing, and in particular to a laser selective melting forming method for large-particle copper and copper alloy powders. Background Art

[0002] Selective laser melting (SLM) technology is a 3D printing technology that uses metal powder to completely melt under the heat of a laser beam, solidify after cooling, and accumulate layer by layer to form a three-dimensional entity. It is widely used in the forming of various high-precision complex components. Its forming process has the characteristics of high forming accuracy, fast forming speed, and adjustable forming quality.

[0003] In the current field of metal 3D printing, SLM technology is mainly used in the forming of high-precision small-size parts, and is constantly developing towards the forming of ultra-high-precision parts.

[0004] However, the copper alloy powder particle size commonly used in the current SLM technology is 15-53μm or 15-60μm. Due to the low forming efficiency, the narrow particle size of the copper alloy powder used and the low powder utilization rate, there is a problem of high printing cost, which restricts the application scope of SLM technology.

[0005] From the perspective of saving raw materials and improving forming efficiency, low-cost additive manufacturing technology is a goal that researchers are constantly pursuing.

[0006] Under the existing additive manufacturing powder preparation technology, the cost of coarse powder is relatively low, and the price is about 1 / 3-1 / 10 of that of commonly used powder.

[0007] However, traditional large-particle copper alloy powders are difficult to form, and simply increasing the energy density cannot make the powder form densely.

[0008] At the same time, the high energy density will cause turbulence in the molten pool, resulting in a large amount of splashing, which will lead to a large number of metallurgical defects in the parts, including pores or inclusions. The lateral airflow inward caused by the vaporization of the molten pool will spheroidize the molten droplets. Copper alloys are very good at dissipating heat. The diameter of the spheres condensed by the molten droplets is much larger than the thickness of the powder layer, which makes it impossible for the scraper to pass through the powder layer and printing cannot be carried out.

[0009] Therefore, providing a large-particle size SLM metal powder additive manufacturing method to achieve large-particle size metal powder SLM is a problem that technical personnel in this field need to solve. Summary of the invention

[0010] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a laser selective melting forming method for large-particle copper and copper alloy powders.

[0011] The invention discloses a laser selective melting forming method for large-particle copper and copper alloy powders, comprising laying raw material powders and laser scanning;

[0012] The particle size of the raw material powder is D, which satisfies 50 μm ≤ D ≤ 250 μm, and 100 μm ≤ D90 ≤ 200 μm, and the powder spreading thickness is t, which satisfies t = 0.5D90 + A, and -10 μm ≤ A ≤ 10 μm;

[0013] The laser scanning is a first laser scanning and a second laser scanning; the energy density of the first laser scanning is E1, and E1 is 40-100 J / mm3; the energy density of the second laser scanning is E2, and E2 is 100-250 J / mm3; and E2:E1=(1.2-4):1 is satisfied;

[0014] The initial melting layer can be obtained after the first laser scanning, and the dense forming layer can be obtained after the second laser scanning.

[0015] In the present invention, D90 means that in the raw material powder, 90% of the particles of the raw material powder have a particle size smaller than this value.

[0016] Furthermore, in the laser selective melting forming method of the present invention, the particle size of the raw material powder is D, which satisfies 60μm≤D≤250μm, and 100μm≤D90≤200μm.

[0017] Furthermore, in the laser selective melting forming method of the present invention, the particle size of the raw material powder is D, which satisfies 70 μm≤D≤250 μm, and 100 μm≤D90≤200 μm.

[0018] Furthermore, in the laser selective melting forming method of the present invention, the particle size of the raw material powder is D, which satisfies 80μm≤D≤250μm, and 100μm≤D90≤200μm.

[0019] Furthermore, in the laser selective melting forming method of the present invention, the particle size of the raw material powder is D, which satisfies 90 μm≤D≤250 μm, and 100 μm≤D90≤200 μm.

[0020] Furthermore, in the laser selective melting forming method of the present invention, the initial melting layer has irregular droplets, and the irregular droplets form pit areas that can allow more light to be reflected; the dense forming layer has continuous and interwoven fish-scale-like melting channels.

[0021] Furthermore, in the laser selective melting forming method of the present invention, in the second laser scanning, the laser absorptivity of the initial melt layer is 1.2 to 2.5 times the laser absorptivity of the raw material powder.

[0022] Furthermore, in the laser selective melting forming method of the present invention, the grains of the target sample composed of the dense forming layer have <111> Select the best orientation.

[0023] Furthermore, the laser selective melting forming method of the present invention comprises the following steps:

[0024] 1) Establish 3D model: set the powder layer thickness t and scanning interval h according to the raw material powder, and then slice to form a slice file, where 0.8D90≤h≤2D90;

[0025] 2) Preparation before printing: Pour the dried raw material powder into the powder tank, install the base plate and scraper, and pre-place the powder;

[0026] 3) Printing: Spread the raw material powder, and then perform the first laser scan and the second laser scan in sequence along the scanning path;

[0027] 4) Rotate according to the preset scanning strategy, continue printing the next layer, and stack layer by layer until the target sample is obtained.

[0028] Furthermore, in the laser selective melting forming method of the present invention, the raw material powder includes any one or more of pure Cu, CuCr alloy, CuNiSi alloy, and CuTi alloy powder.

[0029] Furthermore, in the laser selective melting forming method of the present invention, the oxygen content of the raw material powder is ≤500ppm, and the fluidity is ≤25s / 50g.

[0030] Furthermore, in the laser selective melting forming method of the present invention, the scanning laser power P1 of the first laser scanning is 100 to 400 W, the scanning speed v1 is 200 to 800 mm / s, and the scanning spacing h1 is 0.08 mm to 0.2 mm;

[0031] The scanning laser power P2 of the second laser scanning: P1 = (1-3): 1; the scanning speed v2 = (0.3-1.5) v1, and the scanning spacing h2 = (0.5-1.2) h1.

[0032] Furthermore, in the laser selective melting forming method of the present invention, the inter-layer rotation angle in the preset scanning strategy in step 4) is 30 to 90°.

[0033] Furthermore, in the laser selective melting forming method of the present invention, the relative density of the target sample is greater than 99%.

[0034] Beneficial effects of the present invention:

[0035] The laser selective melting forming method of the present invention is suitable for the laser selective melting forming of large-particle copper and copper alloy powders, and can accurately customize the appropriate process according to the particle size of the raw material powder, and form an initial melting layer first and then obtain a dense forming layer through two laser scans with different energy densities. The relative density of the target sample prepared by the method of the present invention is greater than 99%, which greatly reduces the cost of SLM technology forming, improves the efficiency of SLM forming, and reduces the energy density required for SLM compared to the conventional particle size SLM forming in the prior art (such as 15-53μm or 15-60μm, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the principle of the laser selective melting forming method of the present invention.

[0037] Figure 2 This is a schematic diagram of the scanning process of the laser selective melting forming method described in Example 1 of the present invention.

[0038] Figure 3 This is a microscopic morphology of the powder used in Example 1 of the present invention.

[0039] Figure 4 This is a diagram of the melting channels of the densely formed layer described in Example 1 of the present invention.

[0040] Figure 5 This is the SEM image of the target sample described in Example 1 of the present invention;

[0041] Figure 6 This is the EBSD image of the target sample described in Example 1 of the present invention;

[0042] Figure 7 1 is the XRD diagram of the powder, target sample and aged sample described in Example 1 of the present invention.

[0043] Figure 8 This is a TEM image of the sample after aging described in Example 1 of the present invention. DETAILED DESCRIPTION

[0044] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described in detail with reference to the accompanying drawings. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the specific implementation method, they shall be carried out according to the conventional conditions or the conditions provided by the manufacturer.

[0045] When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of devices and methods consistent with some aspects of the present disclosure as detailed in the appended claims. The terms used in the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.

[0046] The present invention is further described in detail below in conjunction with specific embodiments. Specific implementation method 1.

[0048] A laser selective melting forming method for large-particle copper and copper alloy powders, comprising laying raw material powders and laser scanning;

[0049] The particle size of the raw material powder is D, which satisfies 50 μm ≤ D ≤ 250 μm, and 100 μm ≤ D90 ≤ 200 μm, and the powder spreading thickness is t, which satisfies t = 0.5D90 + A, and -10 μm ≤ A ≤ 10 μm;

[0050] like Figure 1 As shown, the laser scanning is the first laser scanning and the second laser scanning; the energy density of the first laser scanning is E1, and E1 is 40-100 J / mm 3 The energy density of the second laser scan is E2, and E2 is 100-250 J / mm 3 ; and satisfy E2:E1=(1.2~4):1;

[0051] The initial melting layer can be obtained after the first laser scanning, and the dense forming layer can be obtained after the second laser scanning.

[0052] In some other embodiments, the particle size of the raw material powder is D, which satisfies 60 μm≤D≤250 μm, and 100 μm≤D90≤200 μm.

[0053] In some other embodiments, the particle size of the raw material powder is D, which satisfies 70 μm≤D≤250 μm, and 100 μm≤D90≤200 μm.

[0054] In some other embodiments, the particle size of the raw material powder is D, which satisfies 80 μm≤D≤250 μm, and 100 μm≤D90≤200 μm.

[0055] In some other embodiments, the particle size of the raw material powder is D, which satisfies 90 μm≤D≤250 μm, and 100 μm≤D90≤200 μm.

[0056] In some other embodiments, the initial melt layer has irregular melt droplets, which form pit areas that allow more light to be reflected; and the densely formed layer has continuous and interwoven fish-scale-like melt channels.

[0057] In some other embodiments, in the second laser scan, the laser absorptivity of the initial melt layer is 1.2 to 2.5 times the laser absorptivity of the raw material powder.

[0058] In some other embodiments, the grains of the target sample composed of the densely shaped layer have <111> Select the best orientation.

[0059] In some other embodiments, the laser selective melting forming method comprises the following steps:

[0060] 1) Establish 3D model: set the powder layer thickness t and scanning interval h according to the raw material powder, and then slice to form a slice file, where 0.8D90≤h≤2D90;

[0061] 2) Preparation before printing: Pour the dried raw material powder into the powder tank, install the base plate and scraper, and pre-place the powder;

[0062] 3) Printing: Spread the raw material powder, and then perform the first laser scan and the second laser scan in sequence along the scanning path;

[0063] 4) Rotate according to the preset scanning strategy, continue printing the next layer, and stack layer by layer until the target sample is obtained.

[0064] In some other embodiments, the raw material powder includes any one or more of pure Cu, CuCr alloy, CuNiSi alloy, and CuTi alloy powder.

[0065] In some other embodiments, the oxygen content of the raw material powder is ≤500 ppm, and the fluidity is ≤25s / 50g.

[0066] In some other embodiments, the scanning laser power P1 of the first laser scanning is 100-400W, the scanning speed v1 is 200-800mm / s, and the scanning interval h1 is 0.08mm-0.2mm;

[0067] The scanning laser power P2 of the second laser scanning: P1 = (1-3): 1; the scanning speed v2 = (0.3-1.5) v1, and the scanning spacing h2 = (0.5-1.2) h1.

[0068] In some other implementations, the inter-layer rotation angle in the preset scanning strategy in step 4) is 30-90°.

[0069] In some other embodiments, the relative density of the target sample is greater than 99%.

[0070] Embodiment 1:

[0071] A laser selective melting forming method for large-size CuCrZr alloy powder, such as Figure 2 As shown, the following steps are included:

[0072] 1) Establish 3D model: set the powder layer thickness t and scanning interval h according to the raw material powder, and then slice to form a slice file;

[0073] 2) Preparation before printing: Pour the dried raw material powder into the powder tank, install the base plate and scraper, and pre-place the powder;

[0074] 3) Printing: Spread the raw material powder, and then perform the first laser scan and the second laser scan in sequence along the scanning path;

[0075] 4) Rotate according to the preset scanning strategy, continue printing the next layer, and stack layer by layer until the target sample is obtained. The inter-layer rotation angle in the preset scanning strategy is 67°.

[0076] In this embodiment 1, the raw material powder is shown in Table 1 below:

[0077] Table 1 CuCrZr alloy powder

[0078]

[0079] In this embodiment 1, the particle size of the raw material powder is D, 50 μm ≤ D ≤ 250 μm, and D90 = 120 μm; and the flowability of the raw material powder is 13 s / 50 g. Figure 3 shown.

[0080] In this embodiment 1, we use a BLT S200 device with a maximum power of 500 W to prepare the target sample. The laser spot diameter is 100 microns and the laser wavelength is 1070 nanometers.

[0081] The powder spreading thickness is t, which satisfies t=0.5D90+A, and -10 μm≤A≤10 μm; in this embodiment 1, t is 60 μm.

[0082] The laser scanning includes the first laser scanning and the second laser scanning; the energy density of the first laser scanning is E1, and E1 is 40-100 J / mm 3 The energy density of the second laser scan is E2, and E2 is 100-250 J / mm 3 ; and satisfy E2:E1=(1.2~4):1;

[0083] In this embodiment 1, P1=300W, v1=600mm / s, h=1.5×D90=0.18mm, and E1 is 52J / mm 3 The initial melt layer after the first laser scan has irregular droplets, and the irregular droplets form a pit area that allows more light to be reflected. The laser absorptivity of the initial melt layer is 1.2 times that of the raw material powder.

[0084] The initial melted layer is subjected to a second laser scan to obtain a densely formed layer. The second laser scan has a scanning laser power of P2:P1=2:1, a scanning speed of v2=v1, and a scanning interval of h2=h1.

[0085] The energy density E2 of the second laser scan is 104 J / mm 3 The dense forming layer has continuous and interwoven fish scale-like melting channels, such as Figure 4 As shown. And the relative density of the target sample is 99.7%. And the printing time of the target sample is reduced by about 30% compared with the prior art using 15-53 μm powder.

[0086] Conductivity and mechanical properties analysis of target samples:

[0087] like Figure 5 As shown, the sample has two forms, dark and light, and long strip-shaped grains can be seen. The light-colored area shows a small cellular substructure. The dark area is a planar crystal. Due to the rapid temperature change during the SLM process, the high thermal conductivity of the copper alloy and the large temperature gradient, the crystal grows in a planar shape. The sample has fine precipitates, which are divided into uniform spherical particles and irregularly shaped particles. Due to the fast cooling rate of SLM, the precipitated phase Cr has no time to grow during the existence of the molten pool, and the precipitated phase Cr is finally evenly distributed in the copper matrix in the form of fine particles.

[0088] The electrical conductivity of the target sample reaches 27.94% IACS. During the SLM process, due to the high temperature of the molten pool, the melting and cooling speed of the CuCrZr alloy powder is extremely fast, which leads to faster solid solution of Cr and Zr in the Cu matrix and forms a large amount of supersaturated solid solution. This increases the scattering of electrons by solute atoms and reduces the electrical conductivity of the alloy material.

[0089] Aging process: After keeping at 480℃ for 2 hours, air cooling was performed. After aging, the conductivity of the sample increased to 71.15%, which was 152% higher than the target sample without aging. During the aging process, a large number of nanoparticles were precipitated in the copper matrix, which reduced the scattering of electrons by the solute and improved the conductivity.

[0090] The hardness of the target sample is 183HV, and its tensile strength, yield strength and elongation are 290MPa, 201MPa and 27.3%, respectively. During the SLM process, a large amount of supersaturated solid solution is generated, which enhances the strength of the copper substrate. The strength of the sample after aging is significantly improved. Compared with the unaged target sample, the tensile strength and yield strength are 591MPa and 423MPa, respectively, which are increased by 103% and 110%, respectively, while the elongation only decreases by 1.9%. Similarly, the precipitation strengthening of nanoparticles also enhances the mechanical properties of the alloy. In addition, many dislocations were observed in the matrix of the aged sample, such as Figure 7 As shown, dislocation strengthening leads to increased strength of the CuCrZr alloy.

[0091] Microscopic morphology analysis of the target sample: The grains of the target sample composed of the densely formed layer have <111> Preferred orientation, and the grain size of the alloy is further refined, such as Figure 6 shown.

[0092] Figure 7 The XRD spectra of CuCrZr alloy powder, AB and DA are shown. Under different conditions, the diffraction peaks of α-Cu and Cr can be observed. The (111) diffraction peak intensity is the highest in the alloy powder.

[0093] The microstructure of the aged samples was further analyzed using transmission electron microscopy (TEM). Figure 8 As shown in Figure 2, a large number of nanoparticles precipitated in the copper matrix after aging, resulting in a significant increase in the number of precipitates. The size of the zirconium-rich precipitates ranged from 15 to 100 nm, while the nanoscale Cr phase precipitated uniformly.

[0094] Embodiment 2:

[0095] The difference between Example 2 and Example 1 is that E1 is 40 J / mm 3 ; The E2 is 102J / mm 3 ; The relative density of the target sample is 99.3%.

[0096] Embodiment 3:

[0097] The difference between Example 3 and Example 1 is that E1 is 100 J / mm 3 ; The E1 is 148J / mm 3 ; The relative density of the target sample is 99.5%.

[0098] Embodiment 4:

[0099] The difference between Example 4 and Example 1 is that E1 is 52 J / mm 3 ; The E2 is 100 J / mm3 ; The relative density of the target sample is 99.4%

[0100] Embodiment 5:

[0101] The only difference between Example 5 and Example 1 is that E1 is 52 J / mm 3 ; The E1 is 250J / mm 3 ; The relative density of the target sample is 99.3%.

[0102] Embodiment 6:

[0103] The only difference between Example 6 and Example 1 is that the powder spreading thickness t is 50 μm and the relative density of the target sample is 99.4%.

[0104] Embodiment 7:

[0105] The only difference between Example 7 and Example 1 is that the powder spreading thickness t is 70 μm and the relative density of the target sample is 99.1%.

[0106] Embodiment 8:

[0107] The only difference between Example 8 and Example 1 is that the particle size of the raw powder is D, which satisfies 60μm≤D≤250μm, and D90 is 100μm. The flowability of the raw powder is 15.3s / 50g, the powder thickness t is 50μm; the scanning interval h is 150μm, and E1 is 42J / mm 3 ; The E2 is 100 J / mm 3 ; The relative density of the target sample is 99.2%.

[0108] Embodiment 9:

[0109] The difference between Example 9 and Example 1 is that the particle size of the raw powder is D, which satisfies 70μm≤D≤250μm, and D90 is 110μm. The flowability of the raw powder is 15.6s / 50g, the powder thickness t is 50μm; the scanning interval h is 150μm, and E1 is 48J / mm 3 ; The E2 is 102J / mm 3 ; The relative density of the target sample is 99.3%.

[0110] Embodiment 10:

[0111] The difference between Example 10 and Example 1 is that the particle size of the raw powder is D, which satisfies 80 μm ≤ D ≤ 250 μm, and D90 is 120 μm. The flowability of the raw powder is 16 s / 50 g, the powder thickness t is 60 μm, the scanning interval h is 150 μm, and E1 is 54 J / mm 3 ; The E2 is 102J / mm 3 ; The relative density of the target sample is 99.5%.

[0112] Embodiment 11:

[0113] The difference between Example 11 and Example 1 is that the particle size of the raw powder is D, which satisfies 90μm≤D≤250μm, and D90 is 100μm. The flowability of the raw powder is 14.8s / 50g, the powder thickness t is 50μm; the scanning interval h is 150μm, and E1 is 80J / mm 3 , E2 is 144J / mm 3 The final relative density of the target sample is 99.1%.

[0114] Embodiment 12:

[0115] The difference between Example 12 and Example 1 is that the particle size of the raw powder is D, which satisfies 90μm≤D≤250μm, and D90 is 200μm. The flowability of the raw powder is 14.3s / 50g, the powder thickness t is 100μm; the scanning interval h is 300μm, and E1 is 100J / mm 3 , E2 is 200J / mm 3 The final relative density of the target sample is 99.1%

[0116] Embodiment 13:

[0117] The only difference between Example 13 and Example 1 is that the particle size of the raw powder is D, which satisfies 50 μm ≤ D ≤ 200 μm, and D90 is 90 μm. The flowability of the raw powder is 16.3 s / 50 g, the powder thickness t is 40 μm, and E1 is 42 J / mm 3 ; The E2 is 100 J / mm 3 ; The relative density of the target sample is 99.4%.

[0118] Comparative Example 1:

[0119] The raw material powder in Example 1 was formed by conventional SLM, using one laser scan, a laser power of 400 W, a scanning speed of 700 mm / s, and the relative density of the final product was 93.4%.

[0120] The difference between this comparative example 2 and example 1 is that: the E1 is 38 J / mm 3 ; The E2 is 200 J / mm 3 ; Because E1 is too small, the powder is not initially melted and the target sample cannot be printed.

[0121] Comparative Example 3:

[0122] The difference between this comparative example 3 and example 1 is that: the E1 is 110 J / mm 3 ; The E2 is 90J / mm 3 ; E1 is too large, the initial splashing of powder is more obvious, there are too many defects, and the relative density of the target sample is 95.9%.

[0123] Comparative Example 4:

[0124] The difference between this comparative example 4 and example 1 is that: the E1 is 52 J / mm 3 ; The E2 is 80J / mm 3 ; E2 is too small, the powder cannot be completely melted, and the relative density of the target sample is 96.3%.

[0125] Comparative Example 5:

[0126] The difference between this comparative example 5 and example 1 is that: the E1 is 52 J / mm 3 ; The E2 is 260J / mm 3 ; E2 is too large, the splashing of powder during melting is more obvious, and there are too many defects. The relative density of the target sample is 97.4%.

[0127] Comparative Example 6:

[0128] The difference between this comparative example 6 and example 1 is that: the E1 is 100 J / mm 3 ; The E2 is 100 J / mm 3 ; The relative density of the target sample is 95.9%.

[0129] Comparative Example 7:

[0130] The difference between Comparative Example 7 and Example 1 is that the powder spreading thickness t is 40 μm, the powder spreading is too thin, the laser energy is high, the splashing is serious, and the relative density of the target sample is 95.5%.

[0131] Comparative Example 8:

[0132] The only difference between Comparative Example 8 and Example 1 is that the powder spreading thickness t is 80 μm, which is too thick, and the relative density of the target sample is 93.4%.

[0133] Comparative Example 9:

[0134] The only difference between Comparative Example 9 and Example 1 is that when the particle size of the raw material powder is larger than 250 μm, the powder cannot be formed due to the large particle size, resulting in severe splashing.

[0135] Comparative Example 10:

[0136] The difference between this comparative example 10 and example 1 is that the particle size of the raw powder is D, which satisfies 50 μm ≤ D ≤ 250 μm, and D90 is 90 μm. The flowability of the raw powder is 17.5 s / 50 g, the powder thickness t is 45 μm, the scanning spacing h is 135 μm, and E1 is 42 J / mm 3 ; The E2 is 98J / mm 3 ; Because D90 is too low, the powder fluidity is poor and the distribution is uneven, resulting in defects. The relative density of the target sample is 96.4%

[0137] Comparative Example 11:

[0138] The only difference between this comparative example 11 and example 1 is that the particle size of the raw powder is D, which satisfies 50 μm ≤ D ≤ 250 μm, and D90 is 210 μm. The flowability of the raw powder is 15.1 s / 50 g, the powder thickness t is 105 μm, the scanning spacing h is 315 μm, and E1 is 89 J / mm 3 , E2 is 124J / mm 3 Since D90 was too large, there was severe splashing during the printing process, and the final relative density of the target sample was 95.1%.

[0139] Comparative Example 12:

[0140] The difference between this comparative example 12 and example 1 is that the particle size of the raw powder is D, which satisfies 90 μm ≤ D ≤ 250 μm, and D90 is 90 μm. The flowability of the raw powder is 18.3 s / 50 g, the powder thickness t is 45 μm, the scanning spacing h is 135 μm, and E1 is 48 J / mm 3 , E2 is 104J / mm 3 Since the powder distribution is too concentrated and the powder spreading effect is poor, the relative density of the target sample is 93.1% due to the pores.

[0141] Comparative Example 13:

[0142] The only difference between this comparative example 13 and example 1 is that the particle size of the raw powder is D, which satisfies 90 μm ≤ D ≤ 250 μm, and D90 is 210 μm. The flowability of the raw powder is 15.8 s / 50 g, the powder thickness t is 105 μm, the scanning spacing h is 315 microns, and E1 is 89 J / mm 3 , E2 is 144J / mm 3 Since D90 was too large, there was severe splashing during the printing process, and the final relative density of the target sample was 95.4%.

[0143] The present invention is described by the above specific embodiments, and those skilled in the art should understand that various changes and equivalent substitutions can be made to the present invention without departing from the scope of the present invention. The parts not described in detail in the present specification are well-known technologies to those skilled in the art. In addition, various modifications can be made to the present invention for specific situations or specific circumstances without departing from the scope of the present use. Therefore, the present invention is not limited to the specific embodiments disclosed, but should include all implementation methods falling within the scope of the claims of the present invention.

Claims

1. A laser selective melting forming method for large-particle copper and copper alloy powders, characterized in that: Including laying raw material powder and laser scanning; The particle size of the raw material powder is D, which satisfies 50 μm ≤ D ≤ 250 μm, and 100 μm ≤ D90 ≤ 200 μm, and the powder spreading thickness is t, which satisfies t = 0.5D90 + A, and -10 μm ≤ A ≤ 10 μm; The laser scanning includes the first laser scanning and the second laser scanning; the energy density of the first laser scanning is E1, and E1 is 40-100 J / mm 3 The energy density of the second laser scan is E2, and E2 is 100-250 J / mm 3 ; and satisfy E2:E1=(1.2~4):1; The initial melting layer can be obtained after the first laser scanning, and the dense forming layer can be obtained after the second laser scanning.

2. The laser selective melting forming method according to claim 1, characterized in that: The initial melting layer has irregular molten droplets, which form pit areas that allow more light to be reflected; and the dense forming layer has continuous and interwoven fish-scale-shaped melting channels.

3. The laser selective melting forming method according to claim 1, characterized in that: In the second laser scanning, the laser absorptivity of the initial melt layer is 1.2 to 2.5 times the laser absorptivity of the raw material powder.

4. The laser selective melting forming method according to claim 1, characterized in that: The grains of the target sample composed of the densely formed layer have <111> Select the best orientation.

5. The laser selective melting forming method according to any one of claims 1 to 4, characterized in that: The steps include: 1) Establish 3D model: set the powder layer thickness t and scanning interval h according to the raw material powder, and then slice to form a slice file, where 0.8D90≤h≤2D90; 2) Preparation before printing: Pour the dried raw material powder into the powder tank, install the base plate and scraper, and pre-place the powder; 3) Printing: Spread the raw material powder, and then perform the first laser scan and the second laser scan in sequence along the scanning path; 4) Rotate according to the preset scanning strategy and continue printing the next layer, stacking layer by layer until the target sample is obtained.

6. The laser selective melting forming method according to claim 5, characterized in that: The raw material powder includes any one or more of pure Cu, CuCr alloy, CuNiSi alloy, and CuTi alloy powder.

7. The laser selective melting forming method according to claim 6, characterized in that: The raw material powder has an oxygen content of ≤500ppm and a fluidity of ≤25s / 50g.

8. The laser selective melting forming method according to claim 7, characterized in that: The scanning laser power P1 of the first laser scanning is 100-400W, the scanning speed v1 is 200-800mm / s, and the scanning spacing h1 is 0.08mm-0.2mm; The scanning laser power of the second laser scanning is P2:P1=(1-3):1; the scanning speed is v2=(0.3-1.5)v1, and the scanning spacing is h2=(0.5-1.2)h1.

9. The laser selective melting forming method according to claim 8, characterized in that: The inter-layer rotation angle in the preset scanning strategy in step 4) is 30-90°.

10. The laser selective melting forming method according to claim 9, characterized in that: The relative density of the target sample is greater than 99%.

Citation Information

Patent Citations

  • Additive manufacturing method

    CN107470623A

  • A method for manufacturing a copper circuit board pattern by adding materials

    CN109246939A

  • Selective laser melting forming method

    CN110064756A

  • Selective laser melting machining method and application of high-nickel-rich NiTi alloy

    CN113134627A

  • High-power large-layer-thickness selective laser melting forming method

    CN114160809A

Cited By

  • Method for stabilizing powder bed laser melting process

    CN122099367A

  • Method for preparing heat dissipation shell by adopting SLM (selective laser melting) process and heat dissipation shell

    CN122322514A